2018
DOI: 10.3329/cmoshmcj.v17i1.39435
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients Receiving Stroke Rehabilitation in A Tertiary Care Hospital

Abstract: Background: Stroke rehabilitation is a program designed to help the stroke patients to overcome the disability. Few studies have evaluated the profile of stroke patients. To provide information about demographic data & disease pattern among the patients receiving stroke rehabilitation. Methods: A retrospective study was carried out in the Department of Physical Medicine and Rehabilitation (PMR), National Institute of Neuroscience and Hospital (NINSH) Dhaka, Bangladesh for the period of two year from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Monthly family income of patients who were given hospital-based supervised exercise was significantly higher than that of patients whose family caregivers gave home-based therapeutic exercise. In the present study, most of the patients in both groups (>81.0%) had an ischemic stroke, which is consistent with the findings of the other studies [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Monthly family income of patients who were given hospital-based supervised exercise was significantly higher than that of patients whose family caregivers gave home-based therapeutic exercise. In the present study, most of the patients in both groups (>81.0%) had an ischemic stroke, which is consistent with the findings of the other studies [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…The present study aimed to evaluate the efficacy of caregiver training in the rehabilitation of stroke survivors and compare it with the rehabilitation intervention given by physiotherapists. Studies conducted among the Bangladeshi stroke population also reported that most stroke patients were more than 50 years of age group [ 10 , 13 - 15 ]. A predominance of male gender was observed in the present study, which is similar to the findings of a retrospective study conducted at the National Institute of Neuroscience (NINS) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper limb impairment, a reduction or loss of limb function, is one of the most common consequences of acquired brain injury (ABI) [3]. In Bangladesh, ABI due to stroke and trauma is the leading cause of death and disability, representing an immense economic cost to the nation [20].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, ABI due to stroke and trauma is the leading cause of death and disability, representing an immense economic cost to the nation [20]. Over 97% of people with an ABI are diagnosed with some form of limb weakness that affects their ability to independently perform daily activities [3,20]. In addition, there are very few care facilities and professionals [16,20] limiting access to rehabilitation services, which increases the risk of long-term disability [20].…”
Section: Introductionmentioning
confidence: 99%